MENGUJI PERAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI DALAM HUBUNGAN EKUITAS MEREK (BRAND EQUITY) DAN KEPERCAYAN (TRUST) TERHADAP NIAT BELI ULANG (STUDI PADA OLI YAMALUBE DI KOTA SEMARANG) - Paulina Desi Nataliana, 14.05.51.0109; Santoso, Eric (Students' Journal of Economic and Management, 2018)
This study aims to examine and analyze the role of consumer satisfaction as a mediating variable in the relationship of brand equity and trust in repurchase intention.The population in this study were consumers of users of Yamalube Oli products in the city of Semarang, with a total sample of 100 respondents who were taken by taking the technique using purposive sampling. Data analysis method in this study uses multiple linear regression.The results obtained brand equity have a positive effect on customer satisfaction, trust has a positive effect on customer satisfaction, brand equity has a positive effect on repurchase intention, trust has a positive effect on repurchase intention, customer satisfaction has a positive effect on repurchase intention, the findings of the first mediation effect are obtained that consumer satisfaction does not mediate the effect of brand equity on repurchase intention. Keywords: Brand Equity, Trust, Consumer Satisfaction and Repurchase I